Efficient Synthesis of 1,8-dioxooctahydroxanthenes Catalyzed by Melamine Trisulfonic Acid as a Heterogenous and Recyclable Organocatalyst - Albadi, Jalal; Shirini, Farhad; Mansournezhad, Azam (Current Organocatalysis, 2014)
A green and highly efficient method for the synthesis of 1,8-dioxooctahydroxanthenes catalyzed by melamine trisulfonic acid (MTSA) as a heterogenous and recyclable organocatalyst under solvent-free conditions is reported. This procedure provides many advantages such as easy work-up, clean conversions, short reaction times and high yields of the products.
Keywords: 8-dioxooctahydroxanthenes